2009
DOI: 10.1590/s1806-37132009000300011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de tabagismo ativo e passivo em uma população de asmáticos

Abstract: Smoking causes an intense inflammatory reaction in the airways and is associated with worse clinical outcomes in patients with asthma. The objective of this study was to determine the prevalence of active and passive smoking in a population of patients with asthma. The sample of asthma patients (n = 100) consisted of 47 nonsmokers, 33 former smokers, 17 passive smokers and 3 active smokers. Most had moderate or severe asthma. Mean exhaled CO was 9.34 ppb in smokers, 4.19 ppb in passive smokers, 3.98 ppb in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…The prevalence of current smoking was found to be higher in individuals without asthma than in patients with asthma, being lower in severe asthma patients than in mild-to-moderate asthma patients. The low rates of self-reported smoking among asthma patients in the present study are similar to those found in the literature 9 and might be due to the fact that smoking has a negative impact on the clinical status and quality of life of asthma patients, who therefore avoid cigarettes. Because of their disease, patients with asthma are less likely to continue smoking.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The prevalence of current smoking was found to be higher in individuals without asthma than in patients with asthma, being lower in severe asthma patients than in mild-to-moderate asthma patients. The low rates of self-reported smoking among asthma patients in the present study are similar to those found in the literature 9 and might be due to the fact that smoking has a negative impact on the clinical status and quality of life of asthma patients, who therefore avoid cigarettes. Because of their disease, patients with asthma are less likely to continue smoking.…”
Section: Discussionsupporting
confidence: 88%
“…However, the possibility of patient nondisclosure of smoking status should be taken into account. 9 , 11 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An association between smoking status and anxiety/depression was also observed in the present study, since these comorbidities were more frequent in smokers than in nonsmokers and abstinent smokers (p=0.05). Smoking is known to have several harmful effects, such as ventilatory disorders that include sleep obstructive sleep apnea-hypopnea syndrome, which are frequent in individuals with class III obesity (13)(14) . Therefore, the prevention of smoking initiation and smoking cessation are beneficial in the reduction of comorbidities, complications, and mortality, and health care professionals are responsible for detecting, guiding, and treating patients at risk for smoking-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the cut-off level should vary among populations, and that borderline results should be evaluated with care in clinical practice, especially because the level of environmental exposure to tobacco smoke is likely to be high among asthma patients. ( 26 )…”
Section: Discussionmentioning
confidence: 99%